Economic growth and the quality labour market of jobs created: a Brazilian case and some implications to Latin America - Santana, Naja Brandão; Périco, Ana Elisa [UNESP]; Rebelatto, Daisy Aparecida do Nascimento; Mariano, Enzo Barberio [UNESP] (My University, 2014)
An outcome of economic growth is increased employment, but this should not be the only measure to assess a country's labour market, it is also important to verify whether the jobs created are considered good jobs. Thus, this study analyses the Brazilian labour market from 2000 to 2009, in terms of the quantity and quality of jobs generated in this period. To this end, a descriptive analysis was performed, in addition to an evaluation using econometrics and the data envelopment analysis (DEA) technique. The results of the research indicated that the Brazilian labour market is growing in terms of its quality.
Keywords: Brazil; Economic growth; Labour market quality; Latin America; Job creation; Job quality; Employment quality; Employment quantity; Econometrics; Data envelopment analysis; DEA